Anaerobic co-digestion of food waste, human feces, and toilet paper: Methane potential and synergistic effect. (15th July 2019) - Kim, Jaai; Kim, Jinsu; Lee, Changsoo
Highlights: Anaerobic co-digestion of FW, HF, and TP was studied at different mixing ratios. Co-digestion effect on biogas production was assessed by response surface analysis. Effects on both methane yield and synergistic effect of co-digestion were assessed. No antagonistic effect on methane yield was found regardless of the mixing ratio. The major household organic wastes can be treated on site by anaerobic co-digestion. Abstract: The production of human-generated wastes is increasing with the rise in the world's population. Under this scenario, sustainable management of large quantities of waste is becoming an increasingly challenging task. The present study carried out the anaerobic co-digestion of food waste (FW), human feces (HF), and toilet paper (TP) to evaluate its potential for use in the on-site treatment of household organic wastes. The biochemical methane potential (BMP) was determined for these wastes and their mixtures, confirming the effective methanation of each substrate and its mixtures, with FW showing significantly higher BMP than HF or TP. Response surface analysis of the BMP data successfully produced two models describing the effect of the substrate mixing ratio on the overall methane yield and the synergistic effect of co-digestion (in terms of methane yield). The obtained models revealed that methane yield and the synergistic effect of co-digestion are influenced in different ways by variations in the substrate mixing ratio. Importantly, the effect of interactions between individual substrates is not substantial in magnitude regardless of the substrate mixture composition (synergy index close to 1). This indicates that FW, HF, and TP can be co-digested without compromising the overall methane yield (i.e., no antagonistic effect) at any desired substrate mixing ratio, which makes the application of co-digestion in the field more flexible. The overall results suggest that anaerobic co-digestion is a feasible means for the on-site treatment and valorization of mixed FW, HF, and TP, the major household organic wastes.